The drama of history - Gjesdal, Kristin (Oxford University Press, 2021)
Losing Time (The Vikings At Helgeland) – History Adrift; Subjectivity Probed (Peer Gynt) – Ruins of Antiquity (Emperor and Galilean) – Tragedy and Tradition (Ghosts) – Teaching History (An Enemy of The People) – History and Existence (Hedda Gabler) – Concluding Remarks.
9780190070762
Keywords: Ibsen; Henrik; Hegel; Georg Wilhelm Friedrich; Nietzsche; Friedrich Wilhelm; Theater; Drama